«Enhancement of mechanisms of foreign educational documents recognition» - O V Repetskiy; G P Sudakova (Peoples' Friendship University of Russia (RUDN University), 2009)
Establishment of 10 regional centers on evaluation and recognition of educational documents enabled the optimization of the activity of Russian Federal Service for Education and Science Supervision responsible for equivalency recognition as well as delegation of these functions to Russian regions what is quite topical in such a big country as Russia. One of regional centers is situated in Irkutsk city. So far the Center has analyzed foreign student body of Siberian Federal District and developed a database of standard samples of foreign educational documents in the given region (Project № 5381/№ П-334).